Journalism in the regions Central Visayas reporters’ understanding and uses to generative Artificial Intelligence - Perez-Gallardo, Annie Fe G.; Ilagan, Karol Anne M. (Quezon City University of the Philippines, Diliman, 2024)
Philippine Journalism is also composed of the diverse narratives and experiences from different regions, as its stories are also part of the national agenda. Central Visayas stands out among the regions, with over 200 reporters across various platforms inside a dynamic landscape. As the journalism industry evolves, so do its tools, with newsrooms worldwide increasingly integrating Generative Artificial Intelligence into their news production process. This study delves into the acceptance of Central Visayas reporters to embrace Generative Artificial Intelligence by assessing their knowledge and utilization of this new technology. Through the Diffusion of Innovation and the Unified Theory of Acceptance and Use of Technology, it looks into factors influencing their adoption. Employing a mixed-method, exploratory approach, surveys and in-depth interviews with media practitioners and news managers were conducted across the region's four provinces. The findings not only shed light on current practices for improvement but also serve as a guide for future policies in newsrooms across the community press.
Thesis
Keywords: Journalists -- Philippines -- Central Visayas; Artificial intelligence; Journalism -- Philippines -- Central Visayas -- Technological innovations